2012
DOI: 10.1007/s00464-012-2694-5
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymph node ratio as a prognostic factor after laparoscopic total mesorectal excision for extraperitoneal rectal cancer

Abstract: BackgroundThe lymph node ratio (LNR; number of positive nodes divided by total nodes harvested) has been demonstrated to be a prognostic factor in colon cancer, but its role in extraperitoneal rectal cancer is still debated; furthermore, no data are available on laparoscopic rectal resection. The aim of this study was to evaluate the prognostic impact of LNR on long-term outcomes after laparoscopic total mesorectal excision (LTME) for extraperitoneal cancer in consecutive patients with a 5-year minimum follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“… first applied the LNR concept to the outcome of colorectal cancer in 2005. Several subsequent studies have established that the LNR is predictive of outcome , but it has not been established whether the LNR is superior to N1/N2 staging. Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“… first applied the LNR concept to the outcome of colorectal cancer in 2005. Several subsequent studies have established that the LNR is predictive of outcome , but it has not been established whether the LNR is superior to N1/N2 staging. Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The TNM NSCLC staging system currently uses only the anatomic location of LNs to define N status. The LNR has been shown to be an important prognostic factor in several malignancies (13)(14)(15)(16)(17)(18)(19) and may overcome the limitation in the number of LNs sampled. Consistent with this notion Bria et al showed an association between the LNR and lung cancer outcomes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prognostic accuracy of the actual number of positive LNs is potentially restricted (12). The lymph node ratio (LNR)-the number of positive LNs divided by the number of LNs examined-has been suggested to be a more accurate prognostic indicator than the number of LNs with metastasis in different types of cancer including thyroid, gastric, colorectal, and cancer (13)(14)(15)(16)(17)(18)(19).…”
Section: Abstract: Lymph Node Ratio (Lnr)mentioning
confidence: 99%
“…LNR is defined as the number of positive lymph nodes identified divided by the total lymph nodes examined. Lower LNR indicates a better prognosis with a higher overall and disease-free survival [5,7,8]. Some studies have shown LNR to Citation: Jacquelyn Turner, Lampros Liasis, George Malietzis, Ayana Chase, E. Shyam P. Reddy, et al (2017) Prognostic Impact of Lymph Node Ratio in Obstructive Colorectal Cancer.…”
Section: Introductionmentioning
confidence: 99%